Donor-Derived Transmission of Candida auris During Lung Transplantation. (17th May 2017) - Azar, Marwan M; Turbett, Sarah E; Fishman, Jay A; Pierce, Virginia M
Abstract: Candida auris is an emerging, often multidrug-resistant pathogen with important public health implications. Infections are associated with high mortality, and prevention of transmission requires stringent infection control measures, making C. auris a potential barrier to transplantation. We describe the first donor-derived C. auris transmission in a lung transplant recipient.